Statistical evaluation of the effect of hygrothermal aging on the interlaminar shear of GFRP - Dmitrii S. Lobanov; Andrey S. Yankin; Nataliya I. Berdnikova (Fracture and Structural Integrity)
The studies of patterns of changes in properties, accumulation of damages and failure of structural composites after hygrothermal aging represent a relevant and important area. The paper presents the results of mechanical tests for interlaminar shear of specimens of structural glass/epoxy composite electrical use before and after preliminary hygrothermal aging in operating environments (process water, sea water, machine oil) of various duration (15, 30 and 45 days) and various temperatures (22, 60 and 90 oC). The test results were used to statistically evaluate the significance of non-monotonous changes in strength in the case of interlaminar shear after preliminary hygrothermal aging relative to the nominal material using ANCOVA and regression analysis. Such techniques indicated that sea and process water solutions negatively affected the interlaminar shear strength, but their influences were slightly different and strongly depended on the interaction effect between exposure time and solution temperature. Thus, the maximum difference is around 15 % and 12 % after 45 days inside process and sea water respectively at 90 oC. On the contrary, the impact of machine oil led to an increase in strength, but the effect is weaker compared to water solutions (about 6 %).